Phenomenal intentionality - Kriegel, Uriah (Oxford University Press, 2013)
Phenomenal intentionality is supposed to be a kind of directedness of the mind onto the world that is grounded in the conscious feel of mental life. This book of essays explores a number of issues raised by the notion of phenomenal intentionality.
Title from PDF title page (viewed on Apr. 9, 2013).
Keywords: Intentionality (Philosophy); Phenomenology.; Intentionnalité (Philosophie); Phénoménologie.; phenomenology.; PHILOSOPHY -- Mind & Body.; Phenomenology